Local Wisdom in the Historical Formation of Ecotheology Discourse in South Sulawesi - Fadhilah Utami Ilmi Rifai; Roger Allan Cristian Kembuan; Meily Ivane Esther Neman (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study examines the historical formation of ecotheological discourse in South Sulawesi by emphasizing the role of local wisdom rooted in the relationship between religion, humans, and nature, as well as its encounters with Abrahamic religions. Accordingly, the focus of this study is adat (customary traditions) and their dynamics within a historical context, including colonial understandings of local religions. The research employs a descriptive qualitative method with a literature review approach, supported by historical analysis to trace religious conceptions of the relationship between humans and nature. The findings show that local wisdom embedded in indigenous/ancestral religion systems plays an important role in shaping ethical relationships between humans and the natural environment, which later interacted with the theological frameworks of Abrahamic religions (such as Christianity). These interactions produced distinctive forms of discourse, reflecting both continuity and religious adaptation. Ultimately, this study affirms that ecotheology in South Sulawesi is not a new construct but a historically rooted discourse that remains relevant to the development of environmental ethics grounded in local cultural traditions.